The effect of non-tariff barriers reduction on trade of Kazakhstan - A. Aituar; A. Akhmedyarova (Экономика: стратегия и практика, 2021)
This article examines the impact of non-tariff barriers (NTBs) reduction on Kazakhstan’s trade due to the creation of the Eurasian Customs Union (ECU) in 2010. The assessment of the effect of NTBs reduction was carried out using a dynamic gravity model and econometric PMG method. The synchronization of the system of phytosanitary norms and the approval of a unified system of customs regulation have reduced the cost of trade. These innovations have reduced NTBs between ECU countries, which should increase trade flows between countries.According to the model’s estimates, the reduction in NTBs increased Kazakhstan’s imports from the ECU countries by 33% but did not have a significant impact on exports to these countries. That is, on average, Kazakhstani producers benefited less from joining the ECU than producers in other CU countries. These results confirm the findings of reports of international organizations that because of the creation of the ECU, non-tariff barriers between countries have significantly decreased. Unfortunately, Kazakh producers have not been able to take full advantage of the benefits of joining the ECU, and although NTBs between countries have decreased, total exports to ECU countries have not increased. At the same time, the reduction of barriers between countries allowed entrepreneurs from other countries to increase their exports to Kazakhstan (Kazakhstan’s imports) by 33 percent.